Trichoderma and Bradyrhizobium japonicum bioformulates on soy initial growth - Cadore, Luana da Silva; Vey, Rosana Taschetto; Fresinghelli, Jean Carlos Frezingheli de; Dotto, Lucas; Mendes, Francielly Baroni; Silva, Antonio Carlos Ferreira da (Ciência e Natura, 2020)
Bioproducts can act on plant development in a positive, negative or neutral manner, as well as whether there is interaction of these products when used with other biological bioproducts, often used in soybeans such as Bradyrhizobium japonicum. The objective of this work was to evaluate the action of two trichoderma-based and two Bradyrhizobium japonicum-based bioformulates, combined or not, on variables in the early development of soybean plants, free of phytopathogens. The soybean cultivar Nidera 5909 was used and the treatments consisted of four commercial bioformulates, based on Trichoderma harzianum, Trichoderma sp. and two based on Bradyrhizobium japonicum, being tested in association and /or isolated for soybean seed inoculation. For the seedling emergence variable, there was no difference between the treatments tested. By analyzing the leaf variables such as leaf area, shoot length, fresh and dry shoot, the use of liquid B. japonicum results in higher averages compared to the other bioformulates. When evaluating root length, root surface area, root volume and root dry matter the use of bioformulated with Trichoderma sp. as active ingredient presented the highest averages. It was concluded that the use of Trichoderma sp. and Bradyrhizobium japonicum liquid in their isolated form, provide better initial development for soybean crop.